2022
DOI: 10.3389/fmicb.2022.1026991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plant growth promoting activities of indigenous bacteria of phosphate mine wastes, a first step toward revegetation

Abstract: Morocco holds the vast majority of the world’s phosphate reserves, but due to the processes involved in extracting and commercializing these reserves, large quantities of de-structured, nutritionally deficient mine phosphate wastes are produced each year. In a semi-arid climate, these wastes severely hamper plant growth and development leading to huge unvegetated areas. Soil indigenous Plant Growth-Promoting Bacteria (PGPB) play a pivotal role in restauration of these phosphate mining wastes by revegetation, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Bacillus spp. are well-known for their capacity to counter plant pathogens and enhance plant development by producing hydrogen cyanide and catalase ( Mghazli et al, 2022 ). For example, B. paramycoides can effectively enhance soil health by inhibiting the production of harmful soil metabolites and improving soybean tolerance to root rot disease ( Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus spp. are well-known for their capacity to counter plant pathogens and enhance plant development by producing hydrogen cyanide and catalase ( Mghazli et al, 2022 ). For example, B. paramycoides can effectively enhance soil health by inhibiting the production of harmful soil metabolites and improving soybean tolerance to root rot disease ( Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the plant promotion mechanisms showed that the isolate SN-5 Pseudomonas geniculata showed the highest production of IAA and the highest rate of phosphate and zinc solu bilization. In the study of Mghazli et al (2022), conducted an investigation with the objective of isolating, characterizing and identifying autochthonous bacterial strains in vi tro, for the best per forming strains in plants, they performed sequencing and PCR amplification of the 16S rRNA gene using the primers 27f/1492r and fD1/rD1; the results of molecular identification reflected that the 41 isolates, corresponded to the genera Microbacte rium, Bacillus, Acinetobacter, Agro coccus, Brevibacterium, Neobacillus, Paenibacillus, Peribacillus, Pseudarthrobac ter, Stenotrophomonas and Raoultella; all isolates were able to tolerate up to 5% NaCl; Bacillus paramycoides showed the best catalase activity, positive reaction to cellulase synthesis and the highest hydrogen cyanide (HCN) production activity, a compound known for its ability to control and counteract plant pathogens. In this last cluster, the influence of biotic or abiotic factors is analyzed; however, some microorganisms have the capacity to diminish the negative effects of stress, increasing plant tolerance to these factors.…”
Section: Leavesmentioning
confidence: 99%
“…Currently, the implementation of intensive agriculture has led to the development of diseases, nutrient deficits, soil degradation, loss of biodiversity, ero sion, among others (Pandey et al, 2019;Posada et al, 2021). One of the strategies to counteract this problem lies in the use of microorganisms with agricultural potential and among the most promising are plant growth promoting rhizobacteria (PGPR) and arbuscular mycorrhizal fungi (AMF) (Urgiles-Gómez et al, 2021); these microorganisms have the ability to minimize depen dence on chemical fertilizers and pesticides, thus optimizing soil fertility and quality (Zuluaga et al, 2020;Issifu et al, 2022), are also attributed with the ability to offer resistance to pathogens and environmental stress (Tabacchioni et al, 2021) and facilitate the stimulation of plant growth through mechanisms such as biological nitrogen fixation (BNF), phytohormone production, synthesis of antibiotics and organic acids related to plant growth promotion, phosphate solubiliza tion, siderophore production, cellulase and protease synthesis, among others (dos San tos et al, 2022;Mghazli et al, 2022;Sachman-Ruíz et al, 2022).…”
mentioning
confidence: 99%
“…The bacteria used are the following: Raoultella ornithinolytica, (MZ853484.2), Microbacterium resistens (MZ853466.2), and Staphylococcus saprophyticus (OP750262.1), all isolated from a mine highly contaminated with metals and posing major health problems [47] . Escherichia coli (DH5α) was also tested.…”
Section: Evaluation Of Antimicrobial Propertiesmentioning
confidence: 99%
“…Finally, 0.6 cm discs of fungi were placed in the center of each plate and incubated at 25 °C for 4-5 days in the dark. A plate containing only the fungus was used as a control [47] .…”
Section: Antifungal Testmentioning
confidence: 99%